Profile of the pharmacist in the aesthetic health area: narrative review (Research, Society and Development, 2022)
The actions of the pharmacy professional are many and aesthetic health integrates this professional providing him with a performance focused on aesthetics and the benefits of the consumption of cosmetics to improve and enhance beauty, thus providing well-being to the consumer and the validity of the performance professional of the aesthetic pharmacist. The objective of this study is to investigate the main contributions about the performance of the aesthetic pharmacist, the procedures that can be performed, the achievements in the area and how this perpetuates in the life of the consumer in its most diverse aspects. As a methodology, this study was designed as a narrative review, with the aim of presenting the results of abstracts and works already carried out, proposing an updated review of knowledge about the role of the aesthetic pharmacist. As a result, we verified that the pharmacy professional is understood as a bearer of wisdom and a professional adequately trained to perform a range of procedures in the area of ​​aesthetic health, from the discussions carried out between authors it can be stipulated that the area of ​​aesthetic health comprises the many achievements of the pharmacist. A synthesis of the study is presented in which aesthetic health is consolidating itself as an area of activity for professionals graduated in pharmacy, since the curricular base supports the sciences and techniques involved, allowing the use of appropriate therapeutic resources, promoting body aesthetic solutions. and facial features while emphasizing health as a primary benefit.